Minat Pembelian Sayuran Organik di Retail Jakarta Timur (Pengembangan Theory Of Reasoned Action - Maharsi, Rahmania Ratih; Wardiny, Tuty Maria (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Healthy lifestyle trends have recently become popular among the public. People are beginning to shift their consumption patterns from non-organic to organic vegetables. This study aims to examine the influence of knowledge, health consciousness, attitude, subjective norms, and perceived difficulties on the purchase intention of organic vegetables in retail stores in East Jakarta. The basic method used in this research is descriptive and analytical. The study was conducted in East Jakarta, which has several retail stores selling organic vegetables. A total of 120 respondents participated. Instrument testing and data analysis were conducted using SmartPLS 3 software with the Structural Equation Modeling (SEM) method, specifically the Partial Least Squares (PLS) approach. The results showed that knowledge and health consciousness positively influence attitudes toward purchasing organic vegetables in East Jakarta retail stores. Attitude and subjective norms partially have a positive effect on purchase intention, while perceived difficulty partially has a negative effect. From a sharia economic perspective, consuming organic vegetables is considered more aligned with the principles of sustainability and cleanliness, which are consistent with Islamic values such as prudence (al-ḥadhar) and public welfare (maslahah). In sharia economics, the consumption of halal and thayyib (wholesome) products is a fundamental principle, and organic products better fulfill these criteria compared to conventional products that often contain harmful substances. Therefore, the intention to purchase organic vegetables in retail stores can also be seen as a form of consumer awareness in choosing products that are not only healthy but also ethically aligned with sharia economic principles.